A Comparison of Two Computer Access Systems for Functional Text Entry. - DeVries, Rietta Campbell; Deitz, Jean; Anson, Denis (American Journal of Occupational Therapy, 1998)
Objective. Functional written communication, an important goal in the rehabilitation of persons with tetraplegia, frequently is met through the use of personal computers and alternative computer access systems. To make informed decisions about alternative access systems, the therapist needs information on the efficacy of the available choices. The purpose of this study was to investigate the effectiveness of two commercially available systems for text entry, the traditional mouthstick and the Prentke Romich HeadMaster. Method. Participants were a 25-year-old man and 76-year-old woman who both functioned at a C5 neurological level. Neither participant had previous experience with either system for text entry. A single-subject research design was used whereby Participant 1 experienced six phases of treatment (i.e., CBCBCB, where C = mouthstick andB = HeadMaster), and Participant 2 experienced four phases of treatment (i.e., BCBC). Results. Participant 1 achieved a maximum rate of text entry of 5.85 wpm with both the HeadMaster and the mouthstick, whereas Participant 2 achieved a maximum rate of 7.15 wpm with the mouthstick and 4.85 wpm with the HeadMaster. Results from this study were similar to the results from previous comparison studies of persons with severe disabilities who had no experience with alternative computer access systems. Conclusion. Both participants were able to use both systems successfully; however, their respective rates of text entry were too slow to be functional in most employment situations.